2012
DOI: 10.5194/amt-5-1031-2012
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the Single Particle Soot Photometer to different black carbon types

Abstract: Black carbon (BC) is now mainly of anthropogenic origin. It is the dominant light absorbing component of atmospheric aerosols, playing an important role in the earth's radiative balance and therefore relevant to climate change studies. In addition, BC is known to be harmful to human beings making it relevant to policy makers. Nevertheless, the measurement of BC remains biased by the instrument-based definition of BC. The Single Particle Soot Photometer (SP2), allows the measurement of the refractory BC (rBC) m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
263
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 223 publications
(275 citation statements)
references
References 31 publications
12
263
0
Order By: Relevance
“…The community of SP2 users, in concurrence with recent publications Gysel et al, 2011;Laborde, et al, 2012a), have identified fullerene soot as the best SRM for calibrating and comparing the SP2s because of its similarity to ambient refractory black carbon (Fig. 5).…”
Section: Refractory Black Carbon Measurementsmentioning
confidence: 75%
See 1 more Smart Citation
“…The community of SP2 users, in concurrence with recent publications Gysel et al, 2011;Laborde, et al, 2012a), have identified fullerene soot as the best SRM for calibrating and comparing the SP2s because of its similarity to ambient refractory black carbon (Fig. 5).…”
Section: Refractory Black Carbon Measurementsmentioning
confidence: 75%
“…Hence, the established calibration method is to use a differential mobility analyzer (DMA) to select the particles by their mobility diameter. This requires knowledge of the calibration materials effective density (mass -mobility relationship), which may vary from batch to batch (Laborde et al, 2012a). Therefore a central source of well characterized fullerene soot is needed to assure reproducibility and accuracy of SP2 measurements by different research groups.…”
Section: Refractory Black Carbon Measurementsmentioning
confidence: 99%
“…This is the same instrument that was used in previous FAAM publications (McMeeking et al, 2010). It was calibrated using monodisperse AquaDAG (Acheson Industries), with a correction of 0.75 applied according to Laborde et al (2012a). The instrument measures refractory black carbon, denoted as rBC according to the definitions recommended by Petzold et al (2013).…”
Section: Instrumentationmentioning
confidence: 99%
“…The incandescence signal was calibrated (three times, at the beginning, half way through and at the end of the measurement campaign) using mobility size selected fullerene soot particles (Alpha Aesar; #FS12S011) which is recommended for SP2 calibration as it gives similar SP2 responses as ambient rBC Baumgardner et al, 2012;Laborde et al, 2012a). The fullerene soot particles were selected by mobility diameter using a differential mobility analyser (DMA) and the corresponding particle masses were calculated using the effective density data provided in .…”
Section: Calibrationmentioning
confidence: 99%